Prozessentwicklung für die Automatisierung der Herstellung und Anwendung von hochdichten Peptidmicroarrays - Schillo, Sebastian Mathias (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2014)
Peptidemicroarrays consist of a large variety of peptides immobilized on a solid support. Today many processes in the field ultra-high peptide-microarrays are performed manually and lack of reproducibility. Hence within this work three processes are developed for the standard use of peptide-microarrays.